Embracing The Grind: Why We Chose Higher Education Administration; Maybe You Should Too. (September 2018) - Smith-Jackson, Tonya; Bisantz, Ann; Mayhorn, Christopher B.; Kleiner, Brian M.; Babski-Reeves, Kari; McBride, Maranda
Newspapers, broadcast agencies, and social media outlets frequently feature stories about higher education administrators who are terminated, forced to resign, or otherwise removed from their posts. While the events are based in reality, many across the nation, especially the public, faculty and students, might develop a very negative view of what it means to be a leader in higher education administration. Yet, higher education administration could be one of the most rewarding and growth-contributing careers for many. This panel consists of faculty from various universities who made the selfless choice to serve in challenging administrative roles. They will share their experiences; good, bad, and in-between. Discussions will include lessons learned and how to prepare for these positions, with applications to those with academic experience and those who may come from government or industry occupations that afford a degree skills and knowledge transfer to academia. Information will be provided about work-life balance as well.